Gel Formulation of Lemongrass Essential Oil with HPMC and Carbopol Bases - Suryani Tambunan; Teuku Nanda Saifullah Sulaiman (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Lemongrass (Cymbopogon citratus) essential oil is proven to have efficacy as an antibacterial against pathogenic bacteria, such as Staphylococcus aureus. Essential oils was formulate into gel dosage forms with a base combination of HPMC and carbopol. The use of this combination is known to produce a gel with physical properties better than a single use. This research aimed to investigate the effect of variations of HPMC and carbopol to the physical properties of the gel, the concentration of HPMC and carbopol to produce the optimum formula, and the physical stability of essential oil gel of lemongrass during storage. Gel was made by lemongrass essential oil at a concentration of 6% with base of HPMC and carbopol. Each formula were made and tested the physical properties that include organoleptic, homogenity, pH, viscosity, spreadability and adhesiveness. HPMC and carbopol composition were determined through the process of screening and optimization Simplex Lattice Design methods by Design Expert 7.1.5 software. Experimental results and predictions of SLD were verified by testing one sample t-test with a 95% confidence level. The optimum formula gel of lemongrass essential oil consisting of 4.00% HPMC and 1.00% carbopol. The results test of physical properties of lemongrass essential oil gel obtained homogeneous gel with a pH value of 6.00 ± 0.00, viscosity of 280.00 ± 26.46 dPa.S, spreadability of 9.36 ± 0.47 cm2, and adhesiveness of 2.36 ± 0.10 seconds. Lemongrass essential oil gel was stable for 3 cycles of testing include organoleptic, homogeneity, syneresis, pH, adhesion, and the viscosity of the gel. Spreadability of gel was not stable.